2011
DOI: 10.1111/j.1365-2141.2011.08806.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death in children with sickle cell disease in the Netherlands, before the introduction of neonatal screening

Abstract: Summary This study analyzed the mortality and causes of death in sickle cell disease patients in the Netherlands, to provide a baseline for monitoring the effect of the recently introduced neonatal screening programme and to indicate areas of improvement in the care for these patients. All children (<18 years) diagnosed with sickle cell disease in a tertiary hospital from 1985 to 2007 were included. Vital status was determined up to March 2008. A total of 298 children were included: 189 (63%) patients had HbSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
(17 reference statements)
0
27
0
Order By: Relevance
“…[58][59][60][61][62][63] Survival has improved significantly in the last two decades and 94% of children with SCD now survive until the age of 18 years thanks to better surveillance, pneumoccocus vaccination, penicillin prophylaxis and treatment with hydroyurea. 64,65 However, mortality is still significant once patients reach adulthood.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60][61][62][63] Survival has improved significantly in the last two decades and 94% of children with SCD now survive until the age of 18 years thanks to better surveillance, pneumoccocus vaccination, penicillin prophylaxis and treatment with hydroyurea. 64,65 However, mortality is still significant once patients reach adulthood.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…64,65 However, mortality is still significant once patients reach adulthood. 61,66 SCD-associated morbidity and mortality in young adults is largely due to as yet unpreventable complications such as priapism, avascular necrosis, chronic pulmonary impairment, hypertension, stroke and recurrent venoocclusive crises. 58,[67][68][69][70] The only curative approach for SCD is HSCT.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…[1][2][3]12,13 Whether parents in developed countries now perceive the risks of SCD in terms of acute life-threatening events in childhood, decreased life expectancy in adulthood, or decreased overall quality of life is not known. In our study, 65% of parents knew an adult with SCD and 66% reported that seeing adults with SCD made them worry about the quality of their child's future health.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting deformed red blood cells cause anemia and chronic endothelial damage, leading to a variety of acute medical complications (e.g., acute chest syndrome, splenic dysfuction, and stroke), as well as chronic issues (e.g., pain, renal insufficiency, and bony destruction). [1][2][3][4] SCD is a global public health problem, afflicting millions worldwide and more than 80 000 people in the United States alone. [4][5][6][7] Without proper education and prophylactic care, SCD can be life-threatening, particularly early in childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation